Small states: a review of literature and major development problems - Karunasekera, Jackson (Commonwealth Secretariat LondonGB, 1990)
Reviews the evolution of the concept of smallness. Examines the special problems of small islands and the economic vulnerability of small states. Concludes that a major difficulty for the analysis of the probelms of small states is the lack of a universally accepted definition of such countries.